2012
DOI: 10.1021/ja3002666
|View full text |Cite
|
Sign up to set email alerts
|

Polar Dibenzocyclooctynes for Selective Labeling of Extracellular Glycoconjugates of Living Cells

Abstract: Although strain-promoted alkyne-azide cycloadditions (SPAAC) have found wide utility in biological and material sciences, the low polarity and limited water solubility of commonly used cyclooctynes represents a serious shortcoming. To address this problem, an efficient synthetic route has been developed for highly polar sulfated dibenzocyclooctynylamides (S-DIBO) by a Friedel-Crafts alkylation of 1,2-bis(3-methoxyphenyl)ethylamides with trichlorocyclopropenium cation followed by a controlled hydrolysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 42 publications
0
60
0
Order By: Relevance
“…2). S-DIBO was chosen since it does not cross the plasma membrane and therefore avoids conjugation with intracellular glycoproteins (16). In contrast to metabolically labeled cells, Western blot analysis with anti-biotin antibody showed only weak labeling following SEEL with either sialyltransferase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). S-DIBO was chosen since it does not cross the plasma membrane and therefore avoids conjugation with intracellular glycoproteins (16). In contrast to metabolically labeled cells, Western blot analysis with anti-biotin antibody showed only weak labeling following SEEL with either sialyltransferase.…”
Section: Resultsmentioning
confidence: 99%
“…CMP-Neu5Ac9N 3 , S-DIBO-Biotin, Ac 4 ManNAc, and Ac 4 ManNAz were synthesized as previously described (16,30). Vibrio cholerae neuraminidase (type II) was purchased from Sigma Aldrich (N6514).…”
Section: Methodsmentioning
confidence: 99%
“…1), followed by treatment with streptavidin-568. DIBO was chosen for this study because of its ability to detect both intracellular and extracellular glycoconjugates (21,26). Although staining of Golgi, cell surface, and extracellular matrix was detected primarily in control fibroblasts, a striking additional accumulation of sialylated glycoconjugates was observed within intracellular vesicles in NPC1-null (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The first probe was based on annulation of coumarin to BARAC and was developed by Jewett and Bertozzi [29]. Secondly, Friscourt et al [23] reported that the cyclopropenone derivative of Sondheimer diyne unexpectedly forms a highly fluorescent triazole upon a copper-free reaction with azide. Most recently, Lang et al [34] showed that a TAMRA-functionalized tetrazine derivative leads to fivefold to tenfold increase in fluorescence signal, similar to earlier reported for reaction with trans-cyclooctene and norbornene, upon reaction with BCN.…”
Section: Tools To Quantify Spaac Reaction Ratesmentioning
confidence: 99%